Pattern of Poisoning Cases and Poisoning Deaths A Retrospective Studiy Conducted at Raichur Institute of Medical Sciences, Raichur (Indian Journal of Forensic Medicine & Toxicology, 2020)
The present study is a retrospective study conducted in Raichur institute of Medical sciences, RaichurKarnataka. During the study period that is from January 2017 to March 2017, out of 547 medico-legalcases which came to casualty, 164 cases were poisoning. Among 164 poisoning cases, 13 cases died inhospital and postmortem examination is done in mortuary RIMS Raichur hospital. The most common typeof poisoning case in and around the Raichur district was organo-phosphorus poisoning (58.53%) followedby kerosene poisoning (13.41%). Males (55.48%) were the more common victims of the poisoning. Agegroup between 11-20 years (32.92%) was most commonly affected. Majority of poisoning cases was suicidal(84.14%) in manner. In 26.56% the motive for suicidal poisoning was financial crisis leading to depressionand consumption of poisonous substance.